Relationship between Human Resource Information System and Strategic Capability among Employees in Jordanian Companies - Bourini, Islam Faisal (2010)
Information system is expected to drive human resource (HR)'s transition from a focus on human resource management to strategic capability of employee. The information system role not only adds a valuable dimension to the human resource function, but also assists human resource department to be competent. The study investigates relationship between human resource information systems (HRIS) and strategic capability. It attempts to examine the level of human resource information system and strategic capability in private Jordanian companies in the service sector. A survey questionnaire was sent to human resource managers, human resource directors, human resource professionals, and human resource staff in companies based in Jordan. The findings of the study reveal that there is significant relationship between human resource information system and strategic capability. The study also found that the level of HRIS utilization in Jordanian companies is low in terms of characteristic and system appropriateness, where employee seems not to be satisfied with the current human resource information system or maybe there are lacks of understanding of the system. Moreover, the findings of study indicates that the level of strategic capability of employees in Jordanian companies is high for both dimensions of strategic capability; employee morale and employee capability, the respondents were high socialized within employee morale and they are committed to the company. Also Jordanian companies' gains new customers and they care about human resource through empowerment to lead employee to be able to make strategic decision.